Cosmetic catastrophe: A case report of delayed anaphylactic shocklikely following hair dye exposure - Kuraning, Kiran; K M, Ganesh; Prathapan Sarada, Pooja; Suresh Chandan, Garud; Arayamparambil Vijayan , Padmakumar (Indian Journal of Case Reports, 2026)
Hair dye-related allergic reactions are increasingly common, mainly due to para-phenylenediamine (PPD) in permanent hair dyes. Systemic hypersensitivity reactions such as anaphylaxis are rare and may present atypically. We report a 61-year-old man with hypertension and ischemic heart disease who presented with recurrent syncope and hypotension. During intensive care stay, he developed progressive facial, periorbital swelling, and worsening hypotension. History revealed recent hair dye application followed by scalp and facial pruritus, suggesting possible hair dye-induced anaphylaxis. The patient improved with adrenaline, antihistamines, corticosteroids, and fluids. This case highlights the importance of detailed exposure history and early recognition of anaphylaxis in unexplained syncope or shock.